A Quenched Annexin V‐Fluorophore for the Real‐Time Fluorescence Imaging of Apoptotic Processes In Vitro and In Vivo. Issue 24 (28th October 2020) - Kim, Hyunjin; Kim, Hee Yeon; Lee, Eun Young; Choi, Boem Kyu; Jang, Hyonchol; Choi, Yongdoo
Abstract: Annexin‐based probes have long been used to study apoptotic cell death, which is of key importance to many areas of biological research, drug discovery, and clinical applications. Although apoptosis is a dynamic biological event with cell‐to‐cell variations, current annexin‐based probes are impractical for monitoring apoptosis in real‐time. Herein, a quenched annexin V‐near‐infrared fluorophore conjugate (Q‐annexin V) is reported as the first OFF‐ON annexin protein‐based molecular sensor for real‐time near‐infrared fluorescence imaging of apoptosis. Q‐annexin V is non‐fluorescent in the extracellular region, due to photoinduced electron transfer interactions between the conjugated dye and amino acid quenchers (tryptophan and tyrosine). The probe becomes highly fluorescent when bound to phosphatidylserines on the outer layer of cell membranes during apoptosis, thereby enabling apoptosis to be monitored in real‐time in 2D and 3D cell structures. In particular, Q‐annexin V shows superior utility for in vivo apoptosis fluorescence imaging in animal models of cisplatin‐induced acute kidney injury and cancer immune therapy, compared to the conventional polarity‐sensitive pSIVA‐IANBD or annexin V‐Alexa647 conjugates. Abstract : A quenched annexin‐V near‐infrared fluorophore (Q‐annexin V) conjugate is developed as the first OFF‐ON annexin protein‐based molecular sensor for real‐time near‐infrared fluorescence imaging of apoptosis. Q‐annexin V becomes highly fluorescent when bound to phosphatidylserine on the outer layer of cell membranes during apoptosis, thereby enabling apoptosis to be monitored in real‐time in vitro and in vivo.